Improvement of procedure for casing treatment with a Bacillus subtilis Ch-13-based biofungicide to control green mould disease of mushrooms: Application of Bacillus subtilis in mushrooms - Potočnik, Ivana S; Luković, Jelena; Todorović, Biljana; Stepanović, Miloš; Šantrić, Ljiljana; Milijašević-Marčić, Svetlana; Rekanović, Emil (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
A previous study had confirmed good selective features of a biofungicide based on Bacillus subtilis Ch-13 regarding green mould disease control and increase in white  button mushroom (Agaricus bisporus) production. The recommended application rate of the biofungicide in three split doses (30 + 15 + 15 ml m-2) enhanced mushroom yield by 8.41% and control of green mould disease (Trichoderma aggressivum) by 53.57%. A different application procedure of the biofungicide B. subtilis Ch-13 was then further investigated, involving six split doses (6 × 10 ml m-2) of the same total dose of 60 ml which was previously tested in three split doses. The impact of the biofungicide on fruiting body yield and its effectiveness in disease control were evaluated on white button mushroom artificially infected with Trichoderma aggressivum f. europaeum in the experimental mushroom growing room (in vivo). No statistically significant differences in disease control efficacy were found between the fungicide prochloraz (71.08%) and the biofungicide applied either in six split doses (63.05%) or three (58.43%). As for the fungicide/biofungicide positive impact on mushroom production, no statistically significant differences were detected among treatments.  The B. subtilis Ch-13-based biofungicide may be applied in three split doses, as well as in six split applications, depending on the watering or picking schedule during mushroom cultivation, as both schemes showed satisfactory efficacy in disease control and positive effects on mushroom yield.
Keywords: Bacillus subtilis; Trichoderma aggressivumTrichoderma aggressivum; mushroom; biofungicide